The edge of two worlds: A new review and synthesis on Eurasian forest‐steppes. Issue 3 (10th July 2018) - Erdős, László; Ambarlı, Didem; Anenkhonov, Oleg A.; Bátori, Zoltán; Cserhalmi, Dániel; Kiss, Márton; Kröel‐Dulay, György; Liu, Hongyan; Magnes, Martin; Molnár, Zsolt; Naqinezhad, Alireza; Semenishchenkov, Yury A.; et al.
Abstract: Aims: Eurasian forest‐steppes are among the most complex non‐tropical terrestrial ecosystems. Despite their considerable scientific, ecological and economic importance, knowledge of forest‐steppes is limited, particularly at the continental scale. Here we provide an overview of Eurasian forest‐steppes across the entire zone: (a) we propose an up‐to‐date definition of forest‐steppes, (b) give a short physiogeographic outline, (c) delineate and briefly characterize the main forest‐steppe regions, (d) explore forest‐steppe biodiversity and conservation status, and (e) outline forest‐steppe prospects under predicted climate change. Location: Eurasia (29°–56°N, 16°–139°E). Results and Conclusions: Forest‐steppes are natural or near‐natural vegetation complexes of arboreal and herbaceous components (typically distributed in a mosaic pattern) in the temperate zone, where the co‐existence of forest and grassland is enabled primarily by the semi‐humid to semi‐arid climate, complemented by complex interactions of biotic and abiotic factors operating at multiple scales. This new definition includes lowland forest–grassland macromosaics (e.g. in Eastern Europe), exposure‐related mountain forest‐steppes (e.g. in Inner Asia), fine‐scale forest–grassland mosaics (e.g. in the Carpathian Basin) and open woodlands (e.g. in the Middle East). Using criteria of flora, physiognomy, relief and climate, nine main forest‐steppe regions are identified and characterized. Forest‐steppes are not simple two‐phase systems, as they show a high level of habitat diversity, with forest and grassland patches of varying types and sizes, connected by a network of differently oriented edges. Species diversity and functional diversity may also be exceptionally high in forest‐steppes. Regarding conservation, we conclude that major knowledge gaps exist in determining priorities at the continental, regional, national and local levels, and in identifying clear target states and optimal management strategies. When combined with other threats, climate change may be particularly dangerous to forest‐steppe survival, possibly resulting in compositional changes, rearrangement of the landscape mosaic or even the latitudinal or altitudinal shift of forest‐steppes. Abstract : In our synthetic overview of Eurasian forest‐steppes, by collecting diffuse knowledge we provided a formal definition of forest‐steppes, and discussed spatial extents and gradients. We described and delineation the main forest‐steppe regions. We reviewed species and functional diversity of forest‐steppes and outlined their current conservation status and explored the future prospects under predicted climate change.